Penerapan Alur Storyboard dan Desain Background pada Elemen Grafis Interaktif untuk Menunjang Pembelajaran - Rachmawati, Rizka; Swasty, Wirania; Yutia, Syifa Nurgaida; Rysanti, Alya; Fayyaza, Naira Rizqa (Indonesian Journal for Social Responsibility, 2025)
Lihai Islamic Preschool is an early childhood education institution that focuses on the seven center curriculum but has limitations in the quality of interactive educational play tools that support the seven center curriculum. Because of this, interactive graphic elements like busy-boards and busy-books need to be designed. They play important roles in background design and storyboard plot. Both of these aspects are inseparable in interactive books, yet their roles are often overlooked. The design of the background and storyboard significantly influences preschool children's attention, interest, and emotional response to the story; bright colors, textures, and simple interactions are very effective in enhancing their engagement and potentially affecting their understanding and cognitive aspects. Through active collaboration with 13 teachers from Lihai Islamic Preschool, the community service team from Telkom University presents solutions in designing interactive graphic elements that consider production and social aspects. This activity uses interview methods, product experiments, and questionnaires to obtain partner feedback. The final results transferred to the partners are busy boards and books that have storylines and background designs in accordance with the center's approach to supporting interactive play activities for early childhood.